TEKNOLOGI PENGOLAHAN TELUR PINDANG DI NAGARI UJUNG GADING KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Lailatus Siva (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Nagari Ujung Gading is one of the villages in West Pasaman Regency. The population in Nagari Ujung Gading consists of the Minang, Mandailing, and Malays. Generally, the livelihood of the people in this village is farming. From the livestock sector, the majority of the population raises chickens as a side income. A traditional processed egg product that is commonly used by the community is pindang eggs. This egg processing uses a protein tanner with a combination of salting and boiling as egg preservation. Preservation of eggs is useful for extending the shelf life of eggs. This activity is 1. to increase the knowledge, understanding, and skills of the community in processing pindang eggs, 2. to increase the shelf life of eggs through the processing of livestock products, and 3. to increase the income and welfare of the community. This activity was carried out in Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. This activity introduced pindang egg processing technology. The targets of the activities are women and the community in the local nagari. Meanwhile, the target of distributing pindang eggs is children aged <15 years. The activity method used is counseling, training, and evaluation, with the andragogical learning method. The results of the activities obtained indicate that this activity received a positive response from the community. Furthermore, there is an increase in the knowledge and understanding of the community in processing pindang eggs. Participants can also practice making pindang eggs correctly, starting from preparing raw materials, processing products, to products ready for consumption. The children's response was excellent from the taste and colour of the pindang eggs produced. It is hoped that this activity can be carried out sustainably so that the community's knowledge and skills can increase in the processing of pindang eggs derived from these spices.